Efektivitas Intervensi Berbasis Logoterapi untuk Menurunkan Kecemasan pada Lansia Pengidap Diabetes Melitus - Agestiya Maharani; Safaria, Triantoro (Psyche 165 Journal, 2023)
The process of aging is a natural process accompanied by a decrease in physical, psychological and social conditions that interact with each other, this situation has the potential to cause health problems. Patients with chronic diseases such as diabetes mellitus find it difficult to accept their situation, causing constant stress, this certainly affects individual psychological adjustment. Chronic disease causes various kinds of psychological disorders for the elderly, one of which is anxiety. Logotherapy views that negative events that occur in human life can be changed into something more positive if humans use the right attitude, so that new meanings can emerge. Logotherapy can help individuals realize the meaning of their lives, thereby helping individuals overcome neurotic problems such as anxiety. The purpose of this study was to determine the effectiveness of logotherapy-based interventions to reduce anxiety in elderly people with diabetes mellitus. This study uses a type of quantitative approach with experimental methods, using a single case pre-test post-test design. Determination of respondents was carried out through screening using the BAI (Beck Anxiety Inventory) scale for all elderly people enrolled in a chronic disease program at one of the Puskesmas in D. I. Yogyakarta. From the screening results, it was found that 8 elderly participants with diabetes mellitus experienced moderate and severe anxiety. Data collection methods used observation, interviews, focused group discussions and the BAI 21 item scale (as pre-test and post-test). The results of data analysis using the non-parametric test (Wilcoxon test) showed a value of z = -2530 and a value of p = 0.011 (p <0.05 significant). Thus, it can be concluded that logotherapy-based interventions are effective for reducing anxiety in elderly people with diabetes mellitus.